Defect dynamics in crystalline buckled membranes - Pezzutti, Aldo Daniel (2011)
We study the dynamics of defect annihilation in flexible crystalline membranes suffering a symmetry-breaking phase transition. The kinetic process leading the system toward equilibrium is described through a Brazovskii-Helfrich-Canham Hamiltonian. In membranes, a negative disclination has a larger energy than a positive disclination. Here we show that this energetic asymmetry does not only affect equilibrium properties, like the Kosterlitz-Thouless transition temperature, but also plays a fundamental role in the dynamic of defects. Both unbinding of dislocations and Carraro-Nelson "antiferromagnetic" interactions between disclinations slow down the dynamics below the Lifshitz-Safran regime observed in flat hexagonal systems. © 2011 American Physical Society.